Social Protection In The Fulfillment Of Children’s Rights At The Muhammadiyah Child Welfare Institution (LKSA Taman Harapan), Bandung City - Yuningsih, Yuyun; Sumardani, R.; Nur Fadilah Amalia (SAMPURASUN, 2025)
Children are creations of God who need to be protected and whose rights must be fulfilled. The first and foremost party responsible for providing this protection and fulfillment of rights is the family. However, in reality, the fulfillment of children's rights in Indonesia is still far from perfect. Undang-Undang No 35 Tahun 2014 about Child Protection is one of the regulations in force in Indonesia that provides legal certainty in the protection of children's rights. When parents and families are unable to protect the child, the government is obliged to provide protection through child protection institutions. This research focuses on Social Protection in Fulfilling Children's Rights at LKSA Taman Harapan Muhammadiyah in Bandung City. This study uses a qualitative research method, with primary data obtained through in-depth interview guidelines and secondary data from written documents and physical observation at the research site. This study uses purposive sampling techniques. The findings from the field show that the implementation of social protection carried out by LKSA Muhammadiyah includes the following programs: first, physical and health services through facilities provided by the Foundation in cooperation with zakat and charity services at Muhammadiyah Hospital, where all foster children receive free medical care; second, mental-spiritual services to help children develop a balanced and positive personality through Quran memorization activities, congregational prayer, mandatory tahajjud prayer, and daily recitation of one juz; third, educational services, where all foster children receive free education from elementary to high school, and those with academic achievements are awarded scholarships for college; and fourth, skills training services, offering various skill options according to the children’s interests and talents, such as life skills, vocational skills including sewing, cooking, computer skills, and graphic design. In conclusion, the foster children at LKSA Muhammadiyah in Bandung City have received social protection that effectively fulfills their rights as children.